Peran Publik Perempuan di Indonesia (Perspektif Politik dan HAM) - Hisyam, M Ali (Sunan Kalijaga State Islamic University & The Asia Foundation, 2004)
The role of Indonesian women within the public sphere is heatedly discussed. The issuance of the Constitution No. 12/2003 is perceived by some people as a